Análisis de la productividad de la empresa POLICUBIERTAS S.A. - Sánchez Zhinin, Erika Tatiana (2025)
The research project developed aimed to improve operational efficiency at POLICUBIERTAS S.A., thereby having a greater impact on production and sales. The company specializes in the manufacturing and marketing of polycarbonate roofing and has been facing production planning issues over the years. As a result, the development of a master production plan was proposed, providing the company with production planning through time series forecasting, which is performed using mathematical modeling based on the ARIMA method with RStudio. The project was carried out in three main phases: statistical evaluation of historical data, modeling in the RStudio software, and the design of a Master Production Plan. In the first phase, historical data on production and sales were collected and analyzed. This analysis allowed for the identification of patterns and trends, providing a solid foundation for making informed decisions. The use of RStudio facilitated clear visualization through ARIMA mathematical modeling. Time series were presented, time series decomposition was performed using the additive decomposition model, residual analysis was conducted, and the results were detailed through graphs. The appropriate model used for both sales and production were the ARIMA (3,1,1) (0,1,1) [12] model, selected based on the AIC criterion, which indicates the choice of the smallest value as it loses less information and better explains the data. The forecast error calculation resulted in a value of 5.81% in comparison to the actual data and forecasts for 2023.In the final phase, a Master Production Plan was developed, designed to improve planning. This plan enables the management of production scheduling by evaluating in real time and simulating the impact of the implemented improvements. By integrating the information obtained in the previous phases, the Master Production Plan becomes a key tool for strategic management, aimed at the continuous improvement of efficiency in production processes